Pore‐Size Distribution Controls Shape‐Memory Properties on the Macro‐ and Microscale of Polymeric Foams. Issue 11 (9th April 2013) - Sauter, Tilman; Kratz, Karl; Lendlein, Andreas; Lendlein, Andreas
Abstract Open porous foams with identical foam density but different pore‐size distributions (bimodal or monomodal) are prepared from a shape‐memory polyetherurethane (PEU) by thermally induced phase separation. The shape‐memory effect of the two PEU foams is explored by cyclic thermomechanical compression tests and microstructural analysis. The obtained results reveal that the PEU foam with a bimodal pore‐size distribution exhibits an increased shape‐recovery under stress‐free conditions, both on the macro‐ (foam level) as well as the microscale (pore level). While bimodal pore‐size distributions induce microscale bending during compression, buckling occurs in foams with monomodal pore‐size distributions, leading to both a reduced and delayed shape recovery.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>